Peran Dimensi Motivasi Pelayanan Publik Dalam Meningkatkan Komitmen Afektif Pegawai - Iin Agustina; Hafid Aditya Pradesa; Ricky Adi Putranto (Universitas Katolik Soegijapranata, Semarang, 2021)
Organizational commitment is considered as one of the most important results of public service motivation. There is also an important literature from management studies and organizational behavior that emphasizes affective commitment as the main component of organizational commitment. Based on that, the purpose of this study is to examine the role of the dimensions of public service motivation on employee affective commitment. By using a quantitative approach, the research model was built and tested on 179 research respondents, who were public officer work in the area of Bandung, West Java. Multiple regression analysis is used to analyze the data, with the criteria valid for validity and reliability test. The findings showed that of the four dimensions of public service motivation, it was found that only two significantly affected affective commitment, which were variable commitment to the public interest and variable compassion.